Unveiling the pathway to Z-DNA in the protein-induced B–Z transition - Kim, Sook Ho (Nucleic Acids Res, 2018)
Left-handed Z-DNA is an extraordinary conformation of DNA, which can form by special sequences under specific biological, chemical or physical conditions. Human ADAR1, prototypic Z-DNA binding protein (ZBP), binds to Z-DNA with high affinity. Utilizing single-molecule FRET assays for Z-DNA forming sequences embedded in a long inactive DNA, we measure thermodynamic populations of ADAR1-bound DNA conformations in both GC and TG repeat sequences. Based on a statistical physics model, we determined quantitatively the affinities of ADAR1 to both Z-form and B-form of these sequences. We also reported what pathways it takes to induce the B–Z transition in those sequences. Due to the high junction energy, an intermediate B* state has to accumulate prior to the B–Z transition. Our study showing the stable B* state supports the active picture for the protein-induced B–Z transition that occurs under a physiological setting.